A mentira no discurso do paciente e suas ressonâncias no analista - Schivartche, Marcia (2015)
The goal of this research is to understand the function of the lie during psychoanalysis as well as portraying the analyst's role with regards to handling such a report in light of Freudian psychoanalytic theory. The idea behind this study arose from the analyst's difficulty of working with this type of symptom and a subsequent need to further investigate this everyday phenomenon. Therefore, a study on lies was performed, serving as a starting point for the presentation of a clinical case, which inspired this research. Given the difficulty of the transference management for this type of psychopathology, Freud's work was employed as a support to the psychoanalytic technique. Furthermore, the author also presents other psychoanalysts' reports of patient liars, who in turn, offer a better comprehension of the various aspects that may underlie the lie as told by the patient.Thus, this research intends to consider lies within Psychoanalysis